KARSINOMA KANDUNG KEMIH - Senduk, Samuel S.; Rotty, Linda W.A (Jurnal Biomedik : JBM, 2010)
Abstract: We reported a case of bladder carcinoma in a male of 65 years. The main complaints were hematuria, urinary frequency, dysuria, urgency, loss of weight, and pain in the genital area spreading to the lower abdomen. Diagnosis made by clinical, laboratory, and cytological examinations had no result.  Final diagnosis was made by ultrasonography and cystoscopy, associated with transurethral biopsy and histopathological examination. The result was papillary transitional cell carcinoma, class II; and according to TNM it was a superficial bladder carcinoma in stadium at least T1. Transurethral resection of the tumor was done, and intravesical medicine was given (mitomycin C 40 mg once a week for 6 weeks). The patient was advised to stop smoking and drinking coffee. The prognosis was good. Key words: hematuria, bladder tumor, USG, cystoscopy, tansurethral resection.  Abstrak: Telah dilaporkan kasus karsinoma kandung kemih pada seorang laki-laki berusia 66 tahun. Keluhan utama: hematuri, urgensi, disuri, frekuensi, penurunan berat badan, dan nyeri di kemaluan sampai perut bagian bawah. Diagnosis yang ditegakkan berdasarkan pemeriksaan klinis, laboratorium, sitologi tidak memberi hasil positif. Diagnosis pasti ditegakkan berdasar-kan ultrasonografi dan sistoskopi, disertai biopsi transuretral dan pemeriksaan histopatologi.  Hasil yang diperoleh karsinoma sel transisional papiler kelas II, dan berdasarkan TNM sebagai karsinoma kandung kemih  superfisial dengan stadium sekurang-kurangnya T1. Penanganan yang dilakukan adalah reseksi tumor transuretral yang diikuti pemberian obat intravesika (mitomicyn C 40 mg sekali seminggu selama 6 minggu), dan penderita dianjurkan untuk berhenti merokok dan berhenti minum kopi. Prognosis penderita ini baik. Kata kunci: hematuria, tumor kandung kemih, USG, sistoskopi, reseksi transuretral.